Having Hansen’s disease: perceptions of people under treatment - Joyce Mazza Nunes; Eliany Nazaré Oliveira; Neiva Francenely Cunha Vieira (Rev Rene)
Hanses’s disease is a millenary illness, characterized as a public health problem. We developed this study aiming to know the perception of people under Hanses’s disease treatment about their disease. It’s an study with a qualitative approach, developed through a focal group in August 2005 with eight people under treatment for multibacillary Hansen’s disease in the Health Basic Unit, Sobral-CE. The speeches showed that Hanses’s disease is perceived as a bad disease, which causes sadness, fear, shame and discrimination. Being a Hanses’s disease bearer caused psychological suffering and feelings of powerlessness, and men and women had their social role threatened. We suggest the creation of some alternatives that aim to eliminate Hanses’s disease as a public health problem, but also to bring back citizenship and respect for those people.